Risk analysis of GM crops technology in China: Modeling and governance - Hong, J.; Yu, W.; Marinova, Dora; Guo, X. (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
Despite the fact that in the last decade the genetically modified (GM) food technology has produced a major change in the agricultural sector worldwide, the safety of genetically engineered crops continues to be a highly controversial issue. This paper aims at analyzing risks management of GM crops technology in China, such as risk classification, risk generating mechanisms and its governance. Drawing on both general situation of GM crops technology and extensive academic research concerning its safety, we seek to create a three-dimensional model capable of analyzing the extent of harm associated with GM crops technology risks. On the basis of this framework, the risk of GM crops technology can be divided into eight types, depending on the high or low risks levels associated with social harm, technology maturity and economic outcomes. The paper shows that China is currently located in the high risk zone of this model, where the high technological uncertainty associated with the high potential for social harm shows the urgency for better governance. In order to tackle this, the article introduces the Actor-Network Theory (ANT) as a useful tool to explore the risk assessment and governance of GM crops technology in China. It reveals that the Chinese Government is situated in Obligatory Passage Point (OPP) which is the cardinal node in the network. Its administrative sections play different roles by their respective status in the stages of introducing, creating interest, participating in development and overall support for any new technology. Hence in the case of GM technology, the Chinese government can construct an efficient governance mechanism which should be able to balance actors’ interests and reduce or avoid risks induced by GM crops technology in China.